Ghana's Development Finance Institutions : Review of Current Status and Principles for Reform - World Bank Group (World Bank, Washington, DC, 2018)
This study reviews the approach to development finance adopted by Ghana and takes stock of the current situation of development finance institutions (DFIs). The study then articulates a set of key principles relevant to Ghana reflecting international experience. The intention is to provide the basis for dialogue on new approaches to making Ghana’s policies and institutions more consistent with good practices in development finance. The study does not venture into detailed assessment of particular institutions due to the unavailability of required data for such an assessment. The paper primarily focuses on DFIs targeted toward the priority areas of micro, small and medium enterprises (MSMEs) and non-traditional exports, which are relevant for access to finance and the financial inclusion agenda. Particular attention is paid to their targeting, cost-effectiveness, market distortions, and governance. A review of international experience with DFIs finds that cost-effectiveness tends to be greatest and market distortions lowest when development finance is provided on a wholesale basis through commercial financial institutions that bear the risk and are empowered to make loan decisions, based on well-defined and targeted eligibility criteria. Direct intervention by government in allocation and in setting interest rates tends to undermine sustainability, impact, and willingness of beneficiaries to repay funds that they perceive as politically motivated. Ghana’s approach to development was state-led in the post-Independence period through the mid-1960s, and highly interventionist during the 1970s and early 1980s, after a brief period of stabilization. Controls were gradually removed in the late 1980s, and financial policies were liberalized. During the period 1985-2006, the government and the Bank of Ghana (BoG) established a number of institutions to promote and finance MSMEs and exports, especially in agricultural value chains. While the majority operate through private financial institutions, some of these institutions provide finance directly, increasing the cost and risks and reducing effectiveness. Although some of these institutions managed or benefited from donor-supported government projects in the past, little such funding remains available, especially for MSMEs, resulting in low cost-effectiveness and sustainability for some DFIs. Several institutions have come to depend largely on funds from the Export Trade, Agricultural and Industrial Development Fund (EDAIF), which is funded through a levy on imports. However, an interest rate cap of 12.5 percent is imposed on funding provided by EDAIF, which is well below market rates and tends to result in rent-seeking, long delays while applications are vetted, and lack of interest by commercial financial institutions whose earnings are constrained by the interest rate cap.